Nickel-Catalyzed sp3 C–H Bond Activation from Decarboxylative CrossCoupling of α,β-Unsaturated Carboxylic Acids with Amides - Zhang, Jia-Xiang; Wang, Yan-Jing; Wang, Nai-Xing; Zhang, Wei; Bai, Cui-Bing; Li, Yi-He; Wen, Jia-Long (Synlett, 2014)
Nickel-catalyzed functionalization of C(sp3)–H bonds adjacent to a nitrogen atom in amides through decarboxylative cross-coupling of α,β-unsaturated carboxylic acids is reported. A possible reaction mechanism is proposed that involves radical intermediate species.
Keywords: C–H bonds activation; nickel; cross-coupling; amides; radical reaction